Rancang Bangun Sistem Kontrol Dan Monitoring Beban 3 Phasa Pada Panel Distribusi Berbasis Internet Of Things - Sahar, Muzni; pangestu, yoga; Gunawan, Arif; Novia, Hedri (Politeknik Caltex Riau, 2024)
The distribution panel is a place to distribute and distribute electrical energy from the power panel to the load panel (consumer) for both power installations and lighting installations. The main problem with every disturbance or improvement in electricity usage is that people need to come to the area to control and monitoring the panel manually. This research focuses on the design and manufacture of control and monitoring devices at 3 and 1 phase loads, with the method using NodeMCU esp 32/8266 with pzem004t sensor as control and reading of voltage, current and frequency on the panel, which can be viewed and controlled offline at panel or online using the blynk application. The testing of the tool is carried out using a 3-phase motor, PC monitor, fan, laptop charger, and chicken lamp. By turning on the load one by one or simultaneously. From the test results, the tool can turn on and off online through the blynk application and manually using a push button. the results obtained are quite accurate with a maximum error percentage of 8.70%. However, the microcontroller between control and monitoring is used separately.